Developing and evaluating a lay health worker delivered implementation intervention to decrease engagement disparities in behavioural parent training: a mixed methods study protocol. Issue 7 (18th July 2019) - Barnett, Miya; Miranda, Jeanne; Kia-Keating, Maryam; Saldana, Lisa; Landsverk, John; Lau, Anna S
Abstract : Introduction: Behavioural parent training (BPT) programmes are effective in preventing and treating early-onset conduct problems and child maltreatment. Unfortunately, pervasive mental health service disparities continue to limit access to and engagement in these interventions. Furthermore, challenges with parental engagement can impede the successful implementation of evidence-based practices (EBPs) in community settings that serve low-income, ethnic minority families. Lay health workers (LHWs)—individuals without formal mental health training—represent an important workforce to increase engagement, as they are members of the communities they serve. However, the mobilisation of LHWs has not been well studied as an implementation strategy to extend the reach or effectiveness of EBPs in the USA. LHW-delivered implementation interventions that specifically support the engagement of Latinx parents in evidence-based BPT programmes have the potential to improve clinical and implementation outcomes. Methods and analysis: A community-partnered approach will use the Quality Implementation Framework (QIF) to tailor and implement an LHW-delivered implementation intervention that aims to promote Latinx parent engagement in BPT programmes. Steps from the QIF will guide study activities to (1) conduct a mixed methods needs assessment to fit the implementation intervention to the local context, (2) adapt LHW-delivered implementation strategies to promote parent access to and engagement in Parent-Child Interaction Therapy and (3) conduct a hybrid effectiveness-implementation pilot trial to examine the feasibility, acceptability and preliminary effectiveness of the LHW implementation intervention at increasing engagement. Ethics and dissemination: Study procedures have been approved by the Institutional Review Board at the University of California, Santa Barbara. Results will be shared with the community-advisory group, at community-based meetings for other stakeholders involved in the pilot project, and submitted for publication in peer-reviewed journals.